2014
DOI: 10.1021/jp410648p
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Quantum Transport Properties of Substitutionally Doped Double-Walled Carbon Nanotubes

Abstract: A first-principles investigation of the electronic and quantum transport properties of doublewalled carbon nanotubes doped with nitrogen and boron atoms is presented. Concentric nanotube sidewalls separated by the typical graphitic van der Waals bond distance are found to strongly interact upon incorporation of doping atoms in the hexagonal networks. The local perturbation caused by the doping atoms extends over both shells due to a hybridization of their electronic states, yielding a reduction of the backscat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…double‐walled and multi‐walled carbon nanotubes, or stacked layers of graphene). Among the above‐mentioned challenges, wall‐selectivity has received little attention and provides numerous opportunities for establishing and understanding the fundamental properties of nitrogen‐doped nanocarbons and for developing their potential applications …”
Section: Methodsmentioning
confidence: 99%
“…double‐walled and multi‐walled carbon nanotubes, or stacked layers of graphene). Among the above‐mentioned challenges, wall‐selectivity has received little attention and provides numerous opportunities for establishing and understanding the fundamental properties of nitrogen‐doped nanocarbons and for developing their potential applications …”
Section: Methodsmentioning
confidence: 99%
“…The nitrogen embedded into CNTs can take various forms. The most common are graphitic-nitrogen, pyrrolic-nitrogen, pyridinic-nitrogen and molecular N 2 stuck in the interior of CNT structures [18,19,20]. The nitrogen composition largely depends on the solubility of nitrogen in the catalyst nanoparticle during the reaction at a specified temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Among the abovementioned challenges,w all-selectivity has received little attention [15][16][17] and provides numerous opportunities for establishing and understanding the fundamental properties of nitrogen-doped nanocarbons and for developing their potential applications. Among the abovementioned challenges,w all-selectivity has received little attention [15][16][17] and provides numerous opportunities for establishing and understanding the fundamental properties of nitrogen-doped nanocarbons and for developing their potential applications.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Thes ynthesis and characterisation of nitrogendoped fullerenes,c arbon nanotubes,g raphene and graphene nanoribbons have revealed that nitrogen-doped carbon nanostructures are promising materials for electrocatalysis, [2-9, 11, 13, 14] energy conversion and storage, [2, 4-7, 10, 13, 14] and sensing, [13,14] among others.T he synthesis of nitrogen-doped nanocarbons still presents challenges for controlling:( i) the inclusion percent and the distribution of nitrogen within the graphitic lattice;( ii)t he bonding of the nitrogen atoms,a s principally three types of nitrogen (pyridinic, graphitic,a nd pyrrolic) can exist;(iii)wall-selectivity,inthe case of layered nanocarbons (e.g.d ouble-walled and multi-walled carbon nanotubes,orstacked layers of graphene). Among the abovementioned challenges,w all-selectivity has received little attention [15][16][17] and provides numerous opportunities for establishing and understanding the fundamental properties of nitrogen-doped nanocarbons and for developing their potential applications. [3] Herein, we report aw all-and hybridisation-selective synthetic methodology to produce double-walled carbon nanotubes (DWNT) with an inner tube doped exclusively with graphitic nitrogen atoms (Scheme 1).…”
mentioning
confidence: 99%